ChemInform Abstract: Li10SnP2S12: An Affordable Lithium Superionic Conductor. Issue 4 (28th January 2014) - Bron, Philipp; Johansson, Sebastian; Zick, Klaus; Schmedt auf der Guenne, Joern; Dehnen, Stefanie; Roling, Bernhard
Abstract The title compound is prepared from a stoichiometric mixture of Li4SnS4, Li2S, and P2S5 (evacuated quartz tube, 600 °C, 48 h).